Public Procurement Practices and End User Satisfaction in Rubanda District Local Government. - Niwagaba, Bob (Kabale University, 2024)
The study was conducted to examine public procurement practices and end-user satisfaction in Rubanda District Local Government. The objectives that guided the study included; exploring the effect of transparency on the satisfaction of end-users with the procured services, examining the effect of non-discriminatory procurement practices on end-user satisfaction with the procured services, and examining the effect of competition on the satisfaction of end-users with the procured services in Rubanda District Local Government. The study utilized the case study design. Data was collected from 70 respondents. Data was presented using the frequency distribution tables. At the bivariate level, a Pearson correlation matrix was conducted to ascertain the effect between the predictor variables and the dependent variable. A linear regression model was used to fit the data. Research findings from the regression model show that transparency in procurement(R=.463**, P<0.001), competition in procurement ((R=.219, P<0.001), and non-discrimination (R=.493**, P<0.001) have a positive significance on the service delivery in Rubanda district local government. Conclusions were drawn that competition in procurement, transparency, and nondiscrimination in procurement have a positive significant effect on end-user satisfaction. The study recommended that since there is a significant relationship between best procurement practices and public sector performance, the government and its entities should enforce the use of best procurement practices so that the level of compliance with best procurement practices can be raised.